Investigating the similarities and differences between front and back surface cooling for PV panels. (2023) - Panda, Sampurna; Panda, Babita; Jena, Chitralekha; Nanda, Lipika; Pradhan, Arjyadhara
Abstract: There has been a rise in the use of alternative energy sources around the world, and solar photovoltaic (PV) electricity has gained a lot of popularity. However, the PV module's electrical efficiency decreases as its temperature increases, making it critical to find ways to boost the module's performance at high temperatures. The panel's output, efficiency, performance, and longevity all suffer as a result of the increased temperature caused by the sun's absorption. Using cooling devices to reduce cell temperature is one way to keep PV panels from overheating and damaging their performance. An essential operational consideration for solar photovoltaic systems is maintaining a cool working surface to maximize efficiency. Keeping solar modules at the right temperature might increase their useful life lifetime. The discarded heat from the cooling system has numerous potential uses in the residential, commercial, and industrial sectors. Experiments were performed to determine the impact that surface cooling from either the front or the back had on the output performance of a PV array. Water flow at a specific mass rate was utilized to cool the front exterior of the PV system, while wet grass (dry grass with water supply) was used to cool the back surface in back surface cooling. Because of this, the perforated pipe is situated so that water from the tank can flow out of the panel on both of its front faces. The average temperature drop for the experiment was found to be 21.23°. The outcome was a 28.6 percent boost in the panel's power output. The cooled PV module has an average efficiency of 34.96 percent. Both cooling approaches worked well, however the recommended front surface cooling approach had a far more noticeable and beneficial outcome on the energy output of the PV panel.